Determinação experimental, para solos residuais saturados, da variação dos parâmetros de resistência com a deformação axial - Milititsky, Jarbas (1972)
A description of an experimental technique which makes use of the triaxial test apparatus known as the IDS test as developed by Schmertmann. This technique allows us to determine the components of shear strength of soils, according to new definitions. The shear strength at any deformation is divided into the D component (depending on the normal effective stress) and the I component (independent of normal effective stress), which are new definitions of friction strength and cohesion, respectively. Both components are defined according to changes in intergranular stresses, the structure of soil being approximately constant. Results of tests performed with four different residual soils, three in undisturbeb state and one compacted, are presented. Each test is accomplished by using only one specimen, according to this technique.